Polyelectrolyte membrane scaffold sustains growth of neuronal cells. Issue 4 (4th February 2019) - Grzeczkowicz, A.; Gruszczynska‐Biegala, J.; Czeredys, M.; Kwiatkowska, A.; Strawski, M.; Szklarczyk, M.; Koźbiał, M.; Kuźnicki, J.; Granicka, L. H.
Abstract: Cell immobilization within nano‐thin polymeric shells can provide an optimal concentration of biological material in a defined space and facilitate its directional growth. Herein, polyelectrolyte membrane scaffolds were constructed using a layer‐by‐layer approach to determine the possibility of promoting improved growth of rat cortical neuronal cells. Membrane presence was confirmed by Fourier transform infrared spectroscopy, Zeta potential, and atomic force and scanning electron microscopy. Scaffold performance toward neuronal cell growth was assessed in vitro during a 14‐day culture. Cell conditions were analyzed immunocytochemically. Furthermore, western blot and real‐time PCR analyses were used to validate the presence of neuronal and glial cells on the scaffolds. We observed that alginate/chitosan, alginate/polylysine, and polyethyleneimine/chitosan scaffolds promote neuronal growth similarly to the control, poly‐d ‐lysine/laminin. We conclude that membranes maintaining cell viability, integrity and immobilization in systems supporting neuronal regeneration can be applied in neurological disease or wound healing treatment. © 2018 The Authors. Journal of Biomedical Materials Research Part A published by Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 839–850, 2019.